From Physical Violence to Intensified Economic Abuse: Transitions Between the Types of IPV Over Survivors' Life Courses. (July 2021) - Krigel, Karni; Benjamin, Orly
Scholars of intimate partner violence (IPV) cite the various forms of IPV perpetrated by violent male partners to establish their coercive control over women. This scholarship emphasizes IPV's long-term destructive effects on survivors' lives. However, until recently, the role of the state in the relationship between different manifestations of IPV has received little attention, leaving hazy the meaning of absent formal legislation. An opportunity to clarify the significance of this condition lies in Israel, where economic abuse is not yet recognized as grounds for legal and social sanctions. Based on in-depth interviews with 33 IPV survivors, the present study explores state actions involved in transitions between types of violence as revealed in cases of ongoing economic abuse.